Effect of tea polyphenols on α-amylase activity in starch hydrolysis - Nurul Nadiah Ismail; Uthumporn Utra; Cheng, Lai Hoong; Azhar Mat Esa (Penerbit Universiti Kebangsaan Malaysia, 2018)
Tea leaves (Camellia sinensis) contain bioactive compounds that can help prevent certain diseases. In this study, the inhibitory effect of polyphenolic components of different types of tea leaves (green, oolong and black) extracted using different solvents (ethanol, methanol and water) on α-amylase activity of human saliva were investigated in vitro. Total phenolic content (TPC), total flavonoid content (TFC), ferric reducing/antioxidant power and inhibition of free radical scavenging activity by 1,1-diphenyl-2-picrylhydrazyl of the extracts were measured. Content of gallic acid, caffeine and four catechins also were quantified by high performance liquid chromatography. The ethanol extracts had the highest TPC (124.34-231.23 mg gallic acid equivalents (GAE)/g sample), followed by the methanol extracts (124.28-209.76 mg GAE/g sample) and the water extracts (66.89-136.51 mg GAE/g sample). All three solvent extractions of green tea leaves contained the highest TPC, TFC and antioxidant activity, followed by oolong and black tea leaves. Green tea leaves contained higher amounts of catechins than oolong and black tea leaves. All four catechins were detected in green and oolong tea leaves but only gallocatechin gallate was found in black tea leaves. Next, the effect of tea leaves extracts on starch hydrolysis by α-amylase enzyme from human saliva at 37°C was studied. The starches were hydrolyzed with 0.01% enzyme for 240 min and the extent of hydrolysis was determined based on the dextrose equivalent value. The extent of starch hydrolysis by the tea leaves was as follows: green tea > oolong tea > black tea. The low degree of hydrolysis for black tea was due to its strong inhibitory effect on α-amylase activity. Thus, green, oolong and black tea leaves inhibit activity of α-amylase to different degrees due to their differing compositions and structures of phenolic compounds.